Training Modules 1-5: Greenhouse gas emissions basics, policies, reporting and institutional arrangements for Kenya's crop subsector - Bioversity International and International Center for Tropical Agriculture; Ministry of Agriculture and Livestock Development and Fisheries; Kenya Climate Smart Agriculture Multistakeholder Platform (2024)
By the end of this module, participants should be able to: I. Understand the key elements of the carbon cycle and sinks II. Understand the status of the GHGs emissions in the agricultural sector from a global and national perspective III. Identify the sources, and best practices and innovations for reducing GHG emissions in the crop sector